2011
DOI: 10.1080/09540121.2011.630358
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants, lived experiences, and consequences of household food insecurity among persons living with HIV/AIDS on the shore of Lake Victoria, Kenya

Abstract: Food insecurity is a considerable challenge in sub-Saharan Africa, disproportionately affecting persons living with HIV/AIDS. This study investigates the lived experience, determinants, and consequences of food insecurity and hunger among individuals living with HIV/AIDS on the shore of Lake Victoria in Suba District, Kenya. Parallel mixed methods included semi-structured interviews and administration of the Household Food Insecurity Access Scale among a systematic sampling of 67 persons living with HIV/AIDS (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
2
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 33 publications
11
80
2
13
Order By: Relevance
“…Such low diversity diets predispose patients not only to macronutrient undernutrition but also to micronutrient deficits [8]. Poor feeding practices could also be associated with other social demographic disadvantages [21,22]. Studies have revealed a link between poor feeding practices with food insecurity, poverty, and other social demographic characteristics [8].…”
Section: Discussionmentioning
confidence: 99%
“…Such low diversity diets predispose patients not only to macronutrient undernutrition but also to micronutrient deficits [8]. Poor feeding practices could also be associated with other social demographic disadvantages [21,22]. Studies have revealed a link between poor feeding practices with food insecurity, poverty, and other social demographic characteristics [8].…”
Section: Discussionmentioning
confidence: 99%
“…For example, several HIV cohorts in the US and Canada have relied on modified versions of the Radimer-Cornell scale [42][43][44][45][46]. The HFIAS has been used in several HIV cohorts in the US [47,48], and among HIV-positive populations in Zambia, Uganda and Kenya [49][50][51]. The Household Food Security Scale-Short Form (HFSS-SF) was recently applied in cohorts of PLHIV in Tanzania [52] and Vietnam [53].…”
Section: Food and Nutrition Scurity Measuresmentioning
confidence: 99%
“…hombres heterosexuales) pero no en otros (mujeres heterosexuales y varones homosexuales) 8 o bien la relación no existe 6 . Las investigaciones de paí-ses de bajo ingreso son cualitativas [9][10][11][12] o descriptivas 13 y se han realizado en África, mientras que la escasa evidencia epidemiológica muestra que la IA se relaciona positivamente con la no-adherencia al TAR 14,15 ; lo cual puede deberse a los escasos recursos disponibles en esas sociedades.…”
Section: Introductionunclassified